CVP analysis with stochastic price‐demand functions and shortage‐surplus costs* - LAU, AMY HING‐LING; LAU, HON‐SHIANG (Contemporary Accounting Research, 1987)
Abstract. This paper considers CVP analysis in a situation where: (i) a stochastic price‐demand relationship exists for the product, (ii) production quantity fixed at the beginning of the period may not be equal to the actual demand realized in the period, (iii) the difference between production quantity and realized demand results in either shortage or surplus cost. Procedures for determining optimal price level and production quantity are developed for the managerial objectives of maximizing either (i) expected profit, (ii) expected utility, or (iii) probability of achieving a profit target. Résumé. Cet article examine l'analyse des interactions coût‐volume‐profit dans un contexte où: (i) une relation stochastique entre le prix et la demande existe pour le produit, (ii) la quantité de production établie en début de période peut ne pas être égale à la demande réelle atteinte au cours de la période, (iii) la différence entre la quantité fabriquée et la demande atteinte donne lieu à un coût soit de pénurie ou d'excédent. Des procédés de détermination du niveau optimal de prix et de la quantité fabriquée sont élaborés dans le cadre d'objectifs de la direction visant à maximiser soit (i) le bénéfice espéré, (ii) l'utilité espérée, ou (iii) la probabilité d'atteindre un bénéfice cible.